A conceptual framework for scheduling purposes in mass customisation systems: an agent-based approach. (23rd February 2009) - Aydin, Ali Orhan; Tunali, Semra
Effective planning and scheduling in Mass Customisation Systems (MCSs) is a challenging issue due to the complexity related to planning and scheduling activities. Current software applications fail to meet the requirements of these systems in the job scheduling domain. This paper presents a scheduling system denominated the Intelligent Customisation Scheduler Agent (ICSA) and discusses the underlying approaches (i.e., the metaheuristic scheduling approach, the Generic-Bills-of-Materials (GBOM) and agent technologies) employed in developing the system.